Parasitismo natural del hongo verticillium spp. en el control de la roya del cafeto (hemileia vastatrix), en la comunidad nativa Huascayacu Alto Mayo - Montalvan Chanzapa, César (2005)
This work was conducted in the native Huascayacu community, located 30 km from Moyobamba province, left bank of the Río Mayo, San Martín region: here to develop phase field using sequential evaluation of laboratory was conducted in the laboratory of plant pathology of the Department of protection of crops from the University national San Martin Tarapoto. The purpose of this study was to determine the incidence and severity of the coffee rust disease (Helminthosporium vastatnx) and natural parasitism of Verticillium spp., in the various sectors of the C. C. N. N. Huascayacu. After research found the wide dissemination of the rust disease of coffee in the native Huascayacu community, whose incidence level plot was 1 00%; at plant level were observed incidences ranging between 11.5% to 29.8% and severities between grade 1 and 3. Also determined the natural presence of Verticillium spp., in all evaluated plots. The results of the evaluations show that the sector Shigkat and screw presents the highest incidences of coffee, as well as natural parasitism of Verticilllium rust spp.; which would be due to conditions of plantations with respect to age of the crop, carrying out practices or cultural work (pruning of shade, deshierbas) and the environmental conditions that favor the epidemiological development of the pathogen, the plant and the hyperparasitization.